4‐alkoxyethoxy‐N‐octadecyl‐1, 8‐naphthalimide fluorescent sensor for human serum albumin and other major blood proteins: design, synthesis and solvent effect. (19th June 2012) - Wei, Song; Sun, Yang; Tan, Chunlei; Yan, Sen; Guo, Ping; Hu, Xiaoyun; Fan, Jun
Abstract: A series of 4‐alkoxyethoxy‐ N ‐octadecyl‐1, 8‐naphthalimides with intense blue fluorescence were designed and synthesized as polarity and spectrofluorimetric probes for the determination of proteins. In solvents of different polarities, the Stokes shifts of two dyes increased with increasing solvent polarity and fluorescence quantum yields decreased significantly, suggesting that electronic transiting from ground to excited states was π–π * in character. Dipole moment changes were estimated from solvent‐dependent Stokes shift data using a solvatochromic method based on bulk solvent polarity functions and the microscopic solvent polarity parameter ( E T N ). These results were generally consistent with semi‐empirical molecular orbital calculations and were found to be quite reliable based on the fact that the correlation of the solvatochromic Stokes shifts with E T N was superior to that obtained using bulk solvent polarity functions. Fluorescence data revealed that the fluorescence quenching of human serum albumin (HSA) by dyes was the result of the formation of a Dye–HSA complex. The method was applied to the determination of total proteins (HSA + immunoglobulins) in human serum samples and results were in good agreement with those reported by the research institute. Copyright © 2012 John Wiley & Sons, Ltd.